Investigation of Properties of Concrete Produced with Recycled Aggregates - Bayraktar, Oğuzhan Yavuz; Altera, Abdelwahab Z. Amaitik; Bodur, Burak; Kaplan, Gökhan (ACA Publishing, 2021)
The greatest frequently applied construction substantial in the construction sector is concrete. Natural resources are mostly used in concrete production. While environmental resources are being consumed, concrete environmental pollution increases during urban transformation or reconstruction. In sustainable life, environmental damage caused by construction demolition wastes necessitates the use of recovered aggregate. Recycled aggregate is a term used to depict squashed solid, mortar, blocks or black-top from development trash that is reused in other structure ventures. Reused total is delivered by pounding annihilated waste to recover the total. For as far back as not many decades the accessibility of Construction and demolition waste has expanded so a lot of that the solid business has started using it thusly decreasing the number of totals. The goal is to examine the physical properties, (grain size distribution, density and water absorption) and mechanical properties, (for example, compressive strength, flexural strength, modulus of elasticity and splitting tensile strength) and durability properties, (for example, sulfate resistance, freezing and thawing resistance, acid resistance, high temperature effect and abrasion resistance) of recycled aggregate. It is seen that the mechanical and durability conduct of recycled aggregate concrete is optional to that of standard concrete yet with the utilizing various admixture and unique blending approach, required properties can be accomplished.
Keywords: 13. Climate action; 8. Economic growth; 11. Sustainability; 7. Clean energy; 12. Responsible consumption